Review of Moser, Keith, and Ananta Ch. Sukla (eds). Imagination and Art: Explorations in Contemporary Theory. Brill, 2020. (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2022)
Review of Moser, Keith, and Ananta Ch. Sukla (eds). Imagination and Art: Explorations in Contemporary Theory. Brill, 2020.